2002
DOI: 10.1354/vp.39-5-588
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Rest in a Crl:CD (SD)IGS BR Rat

Abstract: Abstract.A nephrogenic rest was found in the kidney of an 11-week-old male Crl:CD (SD)IGS BR rat. Histologically, the rest was within the renal cortical interstitium and consisted of glomeruloid structures (primitive glomeruli) and inconsistently distinct basophilic tubules lined by a single layer of cuboidal to columnar cells and variably bordered by blastemal cells. Nephrogenic rests have not been reported previously in this rat strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This focal lesion did not affect the general architecture of the kidney. The morphologic features of the current lesion were similar to NR described in the rat (Jackson and Kirkpatrick 2002), except for the infiltrative and proliferative nature. Mesfin (1999) reported that, in addition to infiltrative blastemal cells with alveolar and rosette structures, presence of primitive tubules and glomeruli with high mitotic activity, especially in cells arranged in a tubular pattern, is indicative of early NB.…”
Section: Casesupporting
confidence: 75%
See 3 more Smart Citations
“…This focal lesion did not affect the general architecture of the kidney. The morphologic features of the current lesion were similar to NR described in the rat (Jackson and Kirkpatrick 2002), except for the infiltrative and proliferative nature. Mesfin (1999) reported that, in addition to infiltrative blastemal cells with alveolar and rosette structures, presence of primitive tubules and glomeruli with high mitotic activity, especially in cells arranged in a tubular pattern, is indicative of early NB.…”
Section: Casesupporting
confidence: 75%
“…Hyperplastic and neoplastic rest are mitotically active and may show cellular atypia (Beckwith 1993;Lonergan et al 1998). Incipient NR has been reported in a SD rat (Jackson and Kirkpatrick 2002). Mesfin (1999) reported that ILNB of the rat could be equivalent to dormant NR of humans.…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…Nephroblastoma is considered to be associated with its precursor lesions, the nephrogenic rest, characterized by proliferation of the nephrogenic blastemal cell 9 . Several genes are reported to be involved in nephroblastoma tumorigenesis.…”
mentioning
confidence: 99%